PENGARUH INDEKS HARGA SAHAM REGIONAL ASIA PACIFIK TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) - Koapaha, Hartini Pop (JBE (Journal of Business and Economics), 2014)
This study seeks to find out whether the movement of Asia Pacific region stock indexes are affecting the movement of Indeks Harga Saham Gabungan (IHSG). Population of this study are the stock price indices of Hang Seng Index, Kospi index, Nikkei index, ASX index, STI index, and KLSE index. Simple linear regression is used to find out whether Asia Pacific region stock indexes have significant influence toward IHSG.  The findings indicate that Hang Seng index, Kospi index, Nikkei index, ASX index, STI index, and KLSE index have significant influence toward IHSG.